Macrophage membrane-coated nanovesicles for dual-targeted drug delivery to inhibit tumor and induce macrophage polarization - Xin Huang; Lutong Wang; Haoyu Guo; Weiyue Zhang (Bioactive Materials, 2023)
Background: Immunosuppressive M2 macrophages in the tumor microenvironment (TME) can mediate the therapeutic resistance of tumors, and seriously affect the clinical efficacy and prognosis of tumor patients. This study aims to develop a novel drug delivery system for dual-targeting tumor and macrophages to inhibit tumor and induce macrophage polarization. Methods: The anti-tumor effects of methyltransferase like 14 (METTL14) were investigated both in vitro and in vivo. The underlying mechanisms of METTL14 regulating macrophages were also explored in this study. We further constructed the cyclic (Arg-Gly-Asp) (cRGD) peptide modified macrophage membrane-coated nanovesicles to co-deliver METTL14 and the TLR4 agonist. Results: We found that METTL14 significantly inhibits the growth of tumor in vitro. METTL14 might downregulate TICAM2 and inhibit the Toll-like receptor 4 (TLR4) pathway of macrophages, meanwhile, the combination of METTL14 and the TLR4 agonist could induce M1 polarization of macrophages. Macrophage membrane-coated nanovesicles are characterized by easy modification, drug loading, and dual-targeting tumor and macrophages, and cRGD modification can further enhance its targeting ability. It showed that the nanovesicles could improve the in vivo stability of METTL14, and dual-target tumor and macrophages to inhibit tumor and induce M1 polarization of macrophages. Conclusions: This study anticipates achieving the dual purposes of tumor inhibition and macrophage polarization, and providing a new therapeutic strategy for tumors.